ANALISIS HUBUNGAN DINAMIS ANTARA INDEKS HARGA SAHAM BEBERAPA NEGARA, KURS, DAN HARGA MINYAK DUNIA DENGAN INDEKS HARGA SAHAM SEKTOR PROPERTI, 2001:1-2011:12 - , Dino Suharianto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to analyze the dynamic relationship between stock price index some countries, exchange rate and oil prices with stock price index property sector. The method of analysis used is the Vector Autoregressive (VAR). The data used in this study is a secondary data with time intervals (time series) during the period 2001:1-2011:12. Data obtained from the Indonesia Stock Exchange (IDX), Bank Indonesia (BI) and EconStats. Based on the results of the analysis there are no variables stationary at level, all variables in this study have been stationary at first difference level. From the results of cointegration test using the Johansenâs Cointegration Test method, indicating that there is no cointegration at the 95 percent confidence level or Î± = 5 percent. VAR estimation results in the form of differentiation, Showed the greatest variable affecting the stock price index property sector is Kuala Lumpur Stock Exchange Composite Index, Straits Times Index and exchange rates. These results reinforced the impulse response analysis and variance decomposition.